Implementing behaviour change for healthier lifestyles in obese children. Issue 1 (7th February 2013) - Gately, P. J.; Curtis, C.
Summary Obesity is a major public health issue, the scale and consequences of which suggest the need for comprehensive action. It would appear that there is an imbalance between the investment in primary prevention and in secondary prevention in the form of obesity treatment. It is possible that this imbalance has contributed to our lack of progress in treating obese children effectively and at scale. We propose that an obesity centre of excellence that focuses resources on practice‐based evidence on obesity treatment can contribute to progress in this field. Such a model would also provide the necessary capability to build a national scale solution. While limited, there is an evidence base that shows weight loss and weight loss maintenance and broader health and wellbeing outcomes can be achieved in children and young people. As part of the centre of excellence, a broad range of research aligned to key issues, which include poor awareness of weight issues, poor communication and marketing, greater understanding of the key ingredients of successful weight management (especially in different groups), improved methods to assess the impact of interventions and improved translation research to scale up services to meet the significant demand that exists, would all contribute to a more comprehensive solution to the issue of obesity.